Interisland gene flow among populations of the buff‐banded rail (Aves: Rallidae) and its implications for insular endemism in Oceania. (21st February 2017) - Garcia‐R, Juan C.; Joseph, Leo; Adcock, Greg; Reid, Julian; Trewick, Steven A.
Abstract : Studies of fragmented habitat, such as island archipelagos, provide insights into the microevolutionary processes that drive early stages of diversification. Here, we examined genetic variation and gene flow among populations of the widespread buff‐banded rail Gallirallus philippensis in Oceania to understand the factors that promote speciation associated within this bird lineage. We analysed mtDNA Control Region sequences and six microsatellite loci from a total of 152 individuals of buff‐banded rail on islands and continental areas. We used a phylogeographic model‐testing approach and a structured spatial design ranging from within to among archipelagoes in the south Pacific. Buff‐banded rail populations in the Philippines archipelago and nearby Palau and Wallacea had high genetic diversity while those in geographically distant Australia showed lower variation. Other archipelagos sampled were found to have less genetic diversity and included haplotypes closely related to Wallacea (Bismarck, Vanuatu, New Caledonia) or Australia (New Zealand, Samoa, Fiji, Cocos Islands). Nucleotide diversity and allele frequency declined with degree of geographic isolation but haplotype diversity remained more even. However, both nucleotide and haplotype diversities were positively correlated with land area. Microsatellite data for a subset of locations showed moderate to high genetic differentiation and significant pairwise F ST despite a relatively high migration rate. Our results are mostly consistent with a model of abrupt genetic changes due to founder events with multiple dispersals into Australia from Wallacea and Bismarck. Australia has probably been the source of birds for islands in the Pacific. This is shown by decreasing genetic diversity and growing genetic differentiation when distances separating populations increased from Australia. A history of range expansion and divergent natural selection may help explain the existence of numerous sympatric Gallirallus island endemics.